PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS KONTEKSTUALTERHADAP PEMAHAMAN KONSEP PADA MATERI ASAM BASA UNTUK SMA - Nurima Suriyani; Khaeruman Khaeruman; Pahriah Pahriah (P-2623-0291)
Chemistry is a science that is quite difficult to learn, one of them due concepts in chemistry are abstract. There are three characteristics of chemistry, namely the macroscopic, symbolic and abstract (microscopic), it takes learning that is able to integrate the three aspects of macroscopic, symbolic through practicum and microscopic through modeling with interactive multimedia that are expected to produce chemical concepts intact. The purpose of this study was to obtain the characteristics and eligibility of interactive multimedia based on contextual to the conceptual understanding on the acid-base concept for high school. This study was R&D (Research and Development) method. In general, the research carried out in five stages: the potential and problems stage, gather information, product design, product validation and product improvements. The type of data obtained was qualitative and quantitative from expert lecturers, practitioner teachers, and limited testing. The results of expert lecturers got an average of 84.89% categorized as very eligible, the validation results of chemistry teachers got a percentage of 93.74% with a very decent category, and the limited testing results by the 10 students got a percentage of 93.06 % categorized as very eligible. It can be concluded that  interactive multimedia based on contextualto Conceptual Understandingin acid-base concept for the high school was eligible for use.